Dari Arsip ke Algoritma: Transformasi Historiografi Indonesia di Era Artificial Intelligence - Risdayanti Risdayanti; Hikmawati Z; Musafir Pababbari; Dewi Anggraini (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The development of Artificial Intelligence (AI) has significantly transformed historiographical practices through archival digitization, algorithm-assisted historical data processing, and changes in historical research methodologies. This study aims to analyze the transformation of Indonesian historiography in the AI era by examining changes in access to historical sources, the evolving role of historians, and the epistemological challenges emerging within digital historiography. The study employed a qualitative approach using a library research design. Data were collected from books, scholarly articles, policy documents, and other relevant literature, and were analyzed through content analysis involving data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that archival digitization has improved the accessibility, research efficiency, and preservation of historical sources while simultaneously creating challenges related to the digital divide, algorithmic bias, and the oversimplification of historical narratives. The study also reveals that AI does not replace historians but rather redefines their role toward more critical responsibilities in source verification, contextual interpretation, and oversight of technology-assisted historiographical processes. Therefore, the transformation of historiography in the AI era should be accompanied by the strengthening of digital historiographical methodologies, digital literacy, and the active engagement of historians to ensure the validity, integrity, and quality of historical knowledge.